APPLICATION OF CODEIGNITER FRAMEWORK IN DETERMINING THE BEST EMPLOYEES USING THE MOORA METHOD AT THE IBUNDA GENERAL HOSPITAL IN SERANG CITY - Basuki Rakhim Setya Permana; Gagah Dwiki Putra Aryono, Gelard Untirtha Pratama, Ahmad Munawir, Maman Masyhuri (Adisam Publisher, 2024)
This research is based on the need to select the best appropriate employees so that they can maximize employee performance potential. Meanwhile, the process of determining the best employees currently at the